The Effect of Using Multimedia-Based Learning on Motivation and Learning Outcomes - Sausanti Eka Putri; Fitri Alyani (Jurnal Penelitian Pendidikan IPA, 2023)
Science subject is one of the lessons that does not only convey theory, but requires practice to gain direct experience for students. Weak learning motivation in students causes the low quality of student learning outcomes. The objective of this study is to determine whether usage has any effect multimedia-based learning media on student motivation and learning outcomes of sixth-grade students on solar system material. This study is a quantitative descriptive methodology using a control group with a pretest-posttest design. The participants in this study are Elementary school in Bekasi and 56 students were included in the sample. This study's findings show that the experimental class's N-Gain percentage scores were higher than average, which are 48.1% higher in characteristics of learning motivation and in the control class on N-Gain percentage score is only 29.67%. Similar to the learning motivation, the experimental class’s N-Gain percentage score for learning outcomes is 71.02%, while the control class demonstrated a result of 46.58%. As a result, it is possible to conclude that the usage of multimedia-based learning resources has an effect on the sixth-grade students’ solar system science learning motivation and learning outcomes.